2020
DOI: 10.2147/copd.s214410
|View full text |Cite
|
Sign up to set email alerts
|

<p>Translation and Cultural Adaptation of PROactive Instruments for COPD in French and Influence of Weather and Pollution on Its Difficulty Score</p>

Abstract: Introduction:The recently developed daily and clinical visit PROactive physical activity in COPD (PPAC) instruments are hybrid tools to objectively quantify the level of physical activity and the difficulties experienced in everyday life. Our aim was to translate these instruments for the French-speaking chronic obstructive pulmonary disease (COPD) community worldwide and evaluate the influence of weather and pollution on difficulty score. Methods: The translation procedure was conducted following the guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…PA is largely affected by weather. On rainy days, PA is significantly reduced in comparison to non-rainy days [70][71][72][73]. The time spent performing PA of ≥2.0 METs and ≥3.0 METs were 145.6 min and 21.3 min, respectively, on non-rainy days and 92.8 min and 11.1 min on rainy days [70].…”
Section: Weathermentioning
confidence: 92%
See 3 more Smart Citations
“…PA is largely affected by weather. On rainy days, PA is significantly reduced in comparison to non-rainy days [70][71][72][73]. The time spent performing PA of ≥2.0 METs and ≥3.0 METs were 145.6 min and 21.3 min, respectively, on non-rainy days and 92.8 min and 11.1 min on rainy days [70].…”
Section: Weathermentioning
confidence: 92%
“…When the temperature was >22.5 • C, the daily step count fell by −891 steps per 1 • C increase in temperature. Vaidya et al [73] reported that although there was a tendency for the questionnaire-evaluated PA to decrease with higher temperatures, the seasons did not have any influence on the PA score in French COPD patients. Balish et al [74] reported that daily step count increased 316 steps for each 10 • C rise in temperature in Canadian COPD patients.…”
Section: Seasonmentioning
confidence: 97%
See 2 more Smart Citations
“…At the same time, clinical interviews and patient questionnaires alone cannot accurately determine the patient’s true PA level [ 7 ]. To improve this situation, the PROactive consortium proposed that a combination of questionnaires and accelerometric measurements be used to assess the behavior of COPD patients [ 8 , 9 ]. Nevertheless, this approach does not eliminate the drawbacks of accelerometry, and therefore does not resolve the primary clinical concern, which is to accurately and objectively detect extreme inactivity (referred to hereafter as EI) in patients whose PA status initially presents as unclear or equivocal [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%